Anatomic, Arthroscopically Assisted, Mini-Open Fibular Collateral Ligament Reconstruction: An In Vitro Biomechanical Study. (February 2014) - Liu, Ping; Wang, Jianquan; Zhao, Feng; Xu, Yan; Ao, Yingfang
Background: The fibular collateral ligament (FCL) is the primary restraint to varus rotation of the knee joint. Arthroscopic techniques are widely used and minimally invasive, but anatomic arthroscopic reconstruction of an isolated FCL injury has not been reported. Hypothesis: Anatomic reconstruction of an isolated FCL injury can be performed arthroscopically and will restore the knee to near-normal stability. Study Design: Controlled laboratory study. Methods: A total of 12 nonpaired, fresh-frozen cadaveric knees were biomechanically subjected to a 10-N·m varus moment and 5-N·m external and internal rotation torques at 0°, 15°, 30°, 60°, 90°, and 120° of knee flexion, respectively (0° only for varus loading). Testing was performed with an intact and sectioned FCL and also after an anatomic reconstruction of the FCL by arthroscopic technique. Kinematics of each knee under various loading conditions was determined with a robotic universal force/moment sensor testing system. Results: After sectioning, significant increases were found in varus rotation at 0°, 15°, 30°, 60°, 90°, and 120° of knee flexion; in external rotation at 15°, 30°, and 60° of knee flexion; and in internal rotation at 30°, 60°, and 90° of knee flexion. After reconstruction, full recovery of knee stability was observed in varus rotation at 0°, 15°, 30°, and 60°; in external rotation at 0°, 15°, 30°, 60°, 90°, and 120°; and in internal rotation at 0°, 15°, 30°, 60°, 90°, and 120°. When the sectioned and intact FCL knee conditions were compared, significant increases of 3.4° at 90° of flexion and 3.4° at 120° of flexion were found ( P < .001, both conditions); when the reconstructed and sectioned FCL knee conditions were compared, significant decreases of 1.7° at 90° of flexion and 1.7° at 120° of knee flexion were found ( P = .033 and .043, respectively). Conclusion: An anatomic reconstruction of the FCL can be performed by an arthroscopically assisted mini-open technique with an isolated FCL injury, and near-normal stability of the knee can be restored. Clinical Relevance: Anatomic reconstruction of the FCL by an arthroscopically assisted mini-open technique is a viable, less invasive option to treat nonrepairable isolated FCL injury.